Persepsi Positif Guru dan Siswa terhadap Pelaksanaan Pembelajaran Bahasa Indonesia Kurikulum Merdeka di SMA - Utama, Sunu Setiawan; Waluyo, Budi; Anindyarini, Atikah (UNIB Press, 2024)
The Independent Curriculum is a curriculum with diverse intracurricular learning where the content will be more optimal so that students have enough time to explore concepts and strengthen competencies. Likewise, teachers have the freedom to choose various teaching tools so that learning can be adjusted to the learning needs and interests of students. This study aims to describe the perceptions of teachers and students, the implementation of the independent curriculum in Indonesian language learning in high schools as well as the challenges of teachers and students and efforts to solve challenges during the implementation of the independent curriculum in Indonesian language subjects. This study is a qualitative descriptive study, namely data collected in the form of written or spoken words from various informants. The information in this study is Indonesian language teachers, grade 10 and grade 11 students, the principal and vice principal at SMAN 1 Wonosari. Data collection techniques were carried out through interviews and observations. Data analysis was carried out in three stages, namely: data reduction, data presentation, and drawing conclusions. The results of this study are as follows: (1) the majority of teachers and students have a positive perception in the implementation of the independent curriculum and have an understanding that is in accordance with the Independent Curriculum. (2) The implementation of Indonesian language learning is carried out referring to the teaching module and focuses on the implementation of the Pancasila Student Profile as a concept of the independent curriculum. Teachers dominate learning with problem-based learning and project-based learning models. Then, (3) the challenges faced by teachers include: unpreparedness of human resources, the existence of differentiated learning, minimal understanding of digital technology, lack of learning resources, and students who are not focused when receiving learning.